Oxidation of Industrially Important Alcohols by Ce(IV) in H2SO4– A Kinetic Approach - PRABHU, D.V. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of industrially important alcohols, geraniol, 1-phenyl ethanol and benzyl alcohol by Ce(IV) in H2SO4 has been studied in the micellar phase using sodium lauryl sulphate in the temperature range 30-50 ºC. The effect of concentrations of alcohol and Ce(IV) in H2SO4 ionic strength and temperature on the oxidation rate has been studied in details. Ni(II), Cu(II) and Zn(II) ions have been used to catalyze the oxidation of the alcohol to the corresponding carbonyl compounds. The oxidation rate increases with alcohol concentration but decreases with the concentration of the oxidation reagent due to the formation of unreactive [Ce(IV)]2 species at higher concentrations of the oxidizing reagent. The thermodynamic activation parameters have been calculated. The negative values of ΔS* indicate the reorientation of solvent molecules around the rigid activated complex formed during the course of the reaction. A suitable reactive mechanisim has been suggested for the oxidation process.